Healthy Lifestyle Behaviors and Sociodemographic Characteristics Among Medical Students in Indonesia During the New Normal Era: A Cross-Sectional Study - Vionnetta, Sharren Shera; Tanumihardja, Tommy Nugroho; Kristian, Kevin (Kesmas, 2023)
This study aimed to identify medical students’ healthy lifestyle behaviors during the new normal era and to determine its relationship with sociodemographic factors, bearing in mind that, as future physicians and health role models, medical students play an important role in adopting and promoting healthy lifestyle behaviors to reduce the risk of future health problems as well as optimize communities’ health status. This cross-sectional study was conducted at the School of Medicine and Health Sciences of Universitas Katolik Indonesia Atma Jaya, with 111 medical students selected through stratified random sampling. Data were collected using sociodemographic characteristics (sex, residence, year of study, and participation in health promotion training) and the Health-Promoting Lifestyle Profile-II (HPLP-II) questionnaire and analyzed using descriptive and bivariate analyses. The results showed a moderate total HPLP-II score (2.46± 0.37). Interpersonal relations had the highest mean score, and health responsibility had the lowest. A significant difference in the total HPLP-II scores was identified between students participating in health promotion training and those who did not (p-value = 0.049). Further study is needed to explore other factors influencing healthy lifestyle behaviors among medical students.